Takaful Scheme for Mental Health Disorders: A Systematic Literature Review - Khairil Faizal Khairi; Nur Hidayah Laili; Aimi Fadzirul Kamarubahrin (Universitas Negeri Surabaya, 2021)
Wealth management involved cycles which are wealth creation, wealth protection, wealth distribution, wealth purification, and wealth accumulation that must in line with the financial objectives of the individual through their life. The current study is focused on the wealth protection element which a takaful scheme for mental health disorders. However, little was known about it. Thus, the objective of this systematic review was to synthesize findings of trend and population-based studies on takaful scheme for mental health disorders. The aim was to presents an extensive systematic review of takaful schemes for mental health disorders. A systematic review was identified using electronic database searches (Google, PubMed, and Scopus), previous reviews and reference lists to identify articles published between 2010 and 2020. Narrative synthesis and systematic review were performed and reported according to the preferred reporting items statement. The current evidence showed there is less study on takaful schemes for mental health disorders in the period 2010 to 2020. The two main contributions of this paper are its use of a readily-available and powerful new instrument, and its use of extremely large data which gives us the power to takaful scheme for mental health disorders for disaggregated health care services. More good quality of systematic literature with comparable assessment tools is needed.